PENGARUH KECERDASAN EMOSIONAL PEGAWAI TERHADAP KUALITAS PELAYANAN PESERTA PENDIDIKAN DAN PELATIHAN PADA BADAN KEPEGAWAIAN PENDIDIKAN DAN PELATIHAN DAERAH PROVINSI SULAWESI TENGAH - Trisnaningsih, Yuli (Katalogis, 2013)
This research aims at analyzing the influence of emotional intelligence (self-awarenness, self-organizing, motivation, empathy, and social skill) of the staff toward the service quality of education and training participants at the Board of collected by using direct observation technique, and distributing questionnair, interview, and documentation. This research employed quantitative descriptive method. Data were analyzed by adopting simple linier regression. The result of this research showed that : (1) simultaneously and partially, emotional intelligence of the staff had strongly significant influence toward the service quality of participant; (2) simultaneously, it had strongly significant influence if the emotional intelligence of the staff increased, the service quality of education and training participants also increased; meanwhile, partially, it had significant influence that each emotional intelligence dimensionÂ increased, so there was an factor ofÂ emotional intelligence that had significant influence toward the service quality was self-awareness dimension and the smallest was motivation dimension.